Prarancangan Pabrik Akrolein Dari Gliserol Dengan Disain Alat Utama Absorber Akrolein (AB-101) Pada Proses Reaksi Dehidrasi Gliserol - Ilman Azhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Acrolein (C3H4O) is the simplest unsaturated aldehyde compound which can be used as a protective liquid fuel from microorganisms, essential amino acid methionine-making material and as a good separator and dispersing agent, widely used in the ceramic, paper and electroplating industries. The establishment of an acrolein factory made from crude glycerol with a capacity of 36,000,000 kg/year is planned in the city of Dumai, Riau Province, Indonesia. Geographical location is at 1o39.21”S 101o38’56”B. Acrolein production process uses glycerol as a raw material with a dehydration reaction to produce acrolein products. The reaction process is carried out at a temperature of 410 oC and a pressure of 1 bar. The reactor used is a fixed bed multitube reactor with isothermal reactor conditions using ZrO2 catalyst. The main design tool is the acrolein absorber (AB-101) which is used as an acrolein absorber which is evaporated on the flush drum (V-101). The type of absorber column used is a packed bed coulumn with a rasching ring type with ceramic material.Keywords: , Absorber, Acrolein, fixedbed multitube reactor